CFD Application for Solid Propellant Rocket Simulation: A Review - Almayas, Ali; Yaakob, Mohd Saffuan; Abdul Aziz, Faieza; Yidris, Noorfaizal; Ahmad, Kamarul Arifin (CFD Letters, 2021)
The design and testing processes of Solid Propellant Rocket should be done properly to ensure it safe to be used. Prototype testing involve in experimental method to test Solid Propellant Rocket. Few prototypes needed to clarify all the errors because it need to be test several times. It is a time-consuming and cost-consuming process when using experimental method. Other than that, analytic method can be used to solve the engineering problem. Even though the method is difficult and complicated, it has been proven as reliable tools to assists experimentation. Computational Fluid Dynamics (CFD) tool has been used as part of the design tool since the beginning of its existence. This is due to the fact that the tool is cheap but with acceptable accuracy and can be used without any safety issue. This review paper presents a comprehensive coverage on the application of CFD in the solid propellant rocket research. This is an important review as to provide a guideline to the new researchers that want to start research work in this area. This paper will give an insight on the research path and tools that can be used to assist the researchers on their research work.